Peningkatan Hasil Belajar Matematika Materi Luas Lingkaran Melalui Model Pembelajaran Kooperatif Tipe Jigsaw di Kelas VI SD Negeri Dukun 1 Kecamatan Karangtengah Kabupaten Demak - Achmad Sodiq; Nurul Umah; Sudirman Sudirman (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to improve the learning outcomes of mathematics in the area of circles through the Jigsaw cooperative learning model in class VI. This type of research is Classroom Action Research. This Classroom Action Research was carried out for 2 cycles, in each cycle there were 2 meetings with each meeting carried out with one lesson plan. This research consists of planning, action, observation and reflection. The subjects of this study were the sixth grade students of SD Negeri Dukun 1, Karangtengah Subdistrict, Demak Regency, with a total of 34 students, consisting of 18 male students and 16 female students. The data collection tool used is by using an observation sheet for teacher and student activities. Upgrade result Student learning outcomes can be seen in each cycle by using evaluation questions. The results of this classroom action research show that learning using the Jigsaw type cooperative model can improve the mathematics learning outcomes of the area of circle material in class VI. Students experienced an increase in each cycle with an average score in the first cycle of 69.70% with sufficient criteria, while in the second cycle the average score was 85.88% with very good criteria on the student evaluation sheet.